The Influence of Fines Content on the Mechanical Properties of Aggregate Subbase Course Material for Highway Construction using Repeated Load CBR Test - Abid, Adil N.; Salih, Abdulhakim O.; Nawaf, Esraa A. (Al-Nahrain Journal for Engineering Sciences, 2017)
The effect of fines content (material finer than 0.075 mm) on the mechanical properties of subbase course aggregate is studied in this paper. a laboratory tests were carried out using percentage of fines material 5%, 10% and 15% by weight adding to the original subbase aggregate class B according to Iraqi specification (SCRB) which the specification limit the range of fines between 5-15%. The repeated load CBR test was done to study the mechanical properties; accumulative permanent, elastic deformation and equivalent elastic modulus.The RL CBR test was useful technique to assess the influence of fines material and stress level on the equivalent elastic modulus, and on the evolution of deformation. The equivalent modulus increase when adding 5% of fines material in case of plastic fines, but in case of non-plastic the increase continues until adding 10% fines material. Adding fines material also led to change in accumulative permanent deformation, where adding 5% fines material increase the permanent deformation by 36%, 5% for material with plastic fines and 20% for material with non-plastic fines for unsoaked samples. In case of soaked samples permanent deformation increase by 28% and 25% at adding fines material for material with plastic fines where decrease by 1% at adding 5% fines to original granular material with non-plastic fines. The theoretical modeling show that the deformation increase by increasing number of loads repetitions.